The Effectiveness of Risk Based Audit in Financial Institutions - Rita Nurnaningsih; Adolf Z.D. Siahay; M. Dedy Eko Trisyono Safari; Ana Ima Sofana; Burhanuddin Jauhari (Journal Markcount Finance, 2024)
For centuries, conventional financial institutions such as banks and cooperatives have played an important role in the economy. However, advances in technology and digitalization have significantly changed the world's financial landscape. Financial Technology (Fintech) has emerged as a disruptive force offering innovative financial solutions, such as automated investment management, peer-to-peer lending, and digital payments. This research aims to discover and analyze the impact of Fintech on conventional financial management. Specifically, this research aims to assess the impact of Fintech on the efficiency and effectiveness of conventional financial services, assess changes in user behavior in managing their finances due to the convenience offered by Fintech, and discover the challenges and opportunities faced by financial institutions. Mixed methods is an approach that combines quantitative and qualitative approaches in this research. Quantitative data is collected through surveys of financial services users to measure their opinions about Fintech services and their impact on personal financial management. The results of this research show that Fintech has changed conventional financial management. From a user perspective, Fintech has increased the ease and efficiency of accessing and managing financial services, and many users say they are more likely to use Fintech apps and platforms for everyday transactions, managing savings and investments. From the side of conventional financial institutions, this research found that Fintech has increased the amount of money they invest. This study found that Fintech is changing conventional financial management in terms of service efficiency and user behavior. While Fintechs offer more convenience and efficiency, they also force traditional financial institutions to adapt and innovate with new technologies.